A Pilot Study of a Novel Automated Somatosensory Evoked Potential (SSEP) Monitoring Device for Detection and Prevention of Intraoperative Peripheral Nerve Injury in Total Shoulder Arthroplasty Surgery. Issue 3 (July 2019) - Chui, Jason; Murkin, John M.; Drosdowech, Darren
Abstract : Introduction: Peripheral nerve injury is a potentially devastating complication after total shoulder arthroplasty (TSA) surgery. This pilot study aimed to assess the feasibility of using an automated somatosensory evoked potential (SSEP) device to provide a timely alert/intervention to minimize intraoperative nerve insults during TSA surgery. Methods: A prospective, single-arm, observational study was conducted in a single university hospital. The attending anesthesiologist monitored the study participants using the EPAD automated SSEP device and an intervention was made if there was an alert during TSA surgery. The median, radial, and ulnar nerve SSEP on the operative arm, as well as the median nerve SSEP of the nonoperative arm were monitored for each patient. All patients were evaluated for postoperative neurological deficits 6 weeks postoperatively. Results: In total, 21 patients were consented and were successfully monitored. In total, 4 (19%) patients developed intraoperative abnormal SSEP signal changes in the operative arm, in which 3 were reversible and 1 was irreversible till the end of surgery. Median and radial nerves were mostly involved (3/4 patients). The mean cumulative duration of nerve insult (abnormal SSEP) was 21.7±26.2 minutes. Univariate analysis did not identify predictor of intraoperative nerve insults. No patients demonstrated postoperative peripheral neuropathy at 6 weeks. Conclusions: A high incidence (19%) of intraoperative nerve insult was observed in this study demonstrating the feasibility of using an automated SSEP device to provide a timely alert and enable an intervention in order to minimize peripheral nerve injury during TSA. Further randomized studies are warranted. Abstract : Supplemental Digital Content is available in the text.